Dehydration and insulinopenia are necessary and sufficient for euglycemic ketoacidosis in SGLT2 inhibitor-treated rats - Rachel J. Perry (Nature Portfolio, 2019)
The use of sodium-glucose transport protein 2 (SGLT2) inhibitors for the treatment of diabetes has been associated with euglycemic ketoacidosis and increased glucose production and glucagon secretion. Here Perry et al. show that these effects rely on both insulinopenia and dehydration, and thus suggest ways to manage the side effects associated with the use of SGLT2 inhibitors.